Cryptanalysis of nonlinear confusion component based encryption algorithm - Munir, Noor; Khan, Majid; Shah, Tariq; Alanazi, Ammar S.; Hussain, Iqtadar (Integration (Amsterdam), 2021)
Recently many substitution box based encryption algorithms ensuring privacy have been proposed. Many, chaotic map based S-boxes have been generated posing high nonlinearity and strong cryptographic properties. Encryption schemes depending on the substitution box (S-box) only are weak and easily breakable with the help of chosen plaintext and ciphertext attacks. In this work, we have completely cryptanalyzed S-box based encryption scheme successfully by two types of attacks. Cryptanalysis in both types of attacks is performed by only one selected image. Moreover, we have suggested some improvements in the algorithm to defeat attacks. •Recently many substitution box-based encryption algorithms ensuring privacy have been proposed.•Many, chaotic map-based substitution boxes (S-boxes) have been generated posing high nonlinearity and strong cryptographic properties.•Encryption schemes depending on the substitution box (S-box) only are weak and easily breakable with the help of chosen plaintext and ciphertext attacks.•In this work, we have completely cryptanalyzed S-box based encryption scheme successfully by two types of attacks.•Cryptanalysis in both types of attacks is performed by only one selected image.